Examining the Influence of Elementary Teachers’ Innovative Strategies on Intermediate Pupils’ Learning Styles - Sarapil, Misher A.; Hamid, Nadzmina J.; Mastul , Al-Rashiff Hamjilani (The Indonesian Institute of Science and Technology Research, 2025)
This study explored the use of innovative teaching strategies—constructivist, collaborative, reflective, integrative, and inquiry-based—and their influence on the learning styles of intermediate pupils at Yusop Dais Elementary School. A descriptive quantitative design was employed, using a researcher-developed questionnaire for teachers and a student learning style instrument adapted from Abrami and Venkatesh. Findings revealed that most pupils preferred visual learning styles, followed by auditory and kinesthetic. Among the strategies, the constructivist approach was the most frequently applied by teachers. Statistical analysis showed no significant influence of visual and auditory learning styles on the effectiveness of constructivist, collaborative, integrative, or inquiry-based strategies. However, a significant relationship was found between the kinesthetic learning style and the reflective strategy. These findings indicate that while various innovative strategies are commonly used, their effectiveness may vary depending on students’ preferred learning styles. The results underscore the importance of aligning teaching strategies with learners’ needs to improve engagement and academic performance. Teachers are encouraged to consider diverse learning preferences and adapt their instructional approaches accordingly to ensure more inclusive and effective teaching practices.